White-Matter Structural Connectivity in Relation to Humor Styles: An Exploratory Study - Wu, Ching-Lin; Zhong, Suyu; Chan, Yu-Chen; Chen, Hsueh-Chih; He, Yong (Frontiers in Psychology, 2018)
To investigate the potential relationship between white matter microstructure and humor styles, diffusion tensor images of brain white matter and humor style tendencies were obtained from thirty healthy adults. Using connectivity efficiency measures from graph theoretical analysis and controlling for the influence of gender, age, educational level, and the big five personality traits, we preliminarily examined the prediction of humor styles from brain network efficiency. The results showed that the local efficiency within particular brain networks positively predicted a self-enhancing humor style and negatively predicted an aggressive humor style. The node efficiency of the left superior temporal gyrus distinguished the benevolent or hostile way that individuals coped with interpersonal embarrassment. These findings from this exploratory study support the hypothesis that white matter structure influences humor styles, and provide the initial evidence and implications regarding the relationship between biological mechanisms and mental health for future research.